Functional Characterization of Two Variants at the Intron 6—Exon 7 Boundary of the KCNQ2 Potassium Channel Gene Causing Distinct Epileptic Phenotypes - Mosca, Ilaria; Rivolta, Ilaria; Labalme, Audrey; Ambrosino, Paolo; Castellotti, Barbara; Gellera, Cinzia; Granata, Tiziana; Freri, Elena; Binda, Anna; Lesca, Gaetan; DiFrancesco, Jacopo C.; Soldovieri, Maria Virginia; et al. (Frontiers in Pharmacology, 2022)
Pathogenic variants in KCNQ2 encoding for Kv7.2 potassium channel subunits have been found in patients affected by widely diverging epileptic phenotypes, ranging from Self-Limiting Familial Neonatal Epilepsy (SLFNE) to severe Developmental and Epileptic Encephalopathy (DEE). Thus, understanding the pathogenic molecular mechanisms of Kv7.2 variants and their correlation with clinical phenotypes has a relevant impact on the clinical management of these patients. In the present study, the genetic, biochemical, and functional effects prompted by two variants, each found in a non-familial SLNE or a DEE patient but both affecting nucleotides at the KCNQ2 intron 6-exon 7 boundary, have been investigated to test whether and how they affected the splicing process and to clarify whether such mechanism might play a pathogenetic role in these patients. Analysis of KCNQ2 mRNA splicing in patient-derived lymphoblasts revealed that the SLNE-causing intronic variant (c.928-1G>C) impeded the use of the natural splice site, thus leading to a 10-aa Kv7.2 in frame deletion (Kv7.2 p.G310delta10); by contrast, the DEE-causing exonic variant (c.928G>A) only had subtle effects on the splicing process at this site, thus leading to the synthesis of a full-length subunit carrying the G310S missense variant (Kv7.2 p.G310S). Patch-clamp recordings in transiently-transfected CHO cells and primary neurons revealed that both variants fully impeded Kv7.2 channel function, and exerted strong dominant-negative effects when co-expressed with Kv7.2 and/or Kv7.3 subunits. Notably, Kv7.2 p.G310S, but not Kv7.2 p.G310delta10, currents were recovered upon overexpression of the PIP2-synthesizing enzyme PIP5K, and/or CaM; moreover, currents from heteromeric Kv7.2/Kv7.3 channels incorporating either Kv7.2 mutant subunits were differentially regulated by changes in PIP2 availability, with Kv7.2/Kv7.2 G310S/Kv7.3 currents showing a greater sensitivity to PIP2 depletion when compared to those from Kv7.2/Kv7.2 G310delta10/Kv7.3 channels. Altogether, these results suggest that the two variants investigated differentially affected the splicing process at the intron 6-exon 7 boundary, and led to the synthesis of Kv7.2 subunits showing a differential sensitivity to PIP2 and CaM regulation; more studies are needed to clarify how such different functional properties contribute to the widely-divergent clinical phenotypes.